SOME ASPECTS OF IMPROVEMENT OF CRIMINAL AND LEGAL STRUGGLE FOR TERRORISM AND EXTREMISM IN THE REPUBLIC OF KAZAKHSTAN (International relations and international law Journal, 2016)
Some suggestions are made regarding the development of the criminal law related to the ﬁ ght against terrorism and extremism in Kazakhstani legislation taking into the criminal law related to the ﬁ ght against terrorism and extremism in Kazakhstani legislation taking into account conventional and regional laws in CIS.
Keywords: terrorism; extremism